2015
DOI: 10.1111/dom.12485
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐level meta‐analysis of the EDITION 1, 2 and 3 studies: glycaemic control and hypoglycaemia with new insulin glargine 300 U/ml versus glargine 100 U/ml in people with type 2 diabetes

Abstract: AimsTo conduct a patient-level meta-analysis of the EDITION 1, 2 and 3 studies, which compared the efficacy and safety of new insulin glargine 300 U/ml (Gla-300) with insulin glargine 100 U/ml (Gla-100) in people with type 2 diabetes (T2DM) on basal and mealtime insulin, basal insulin and oral antihyperglycaemic drugs, or no prior insulin, respectively.MethodsThe EDITION studies were multicentre, randomized, open-label, parallel-group, phase IIIa studies, with similar designs and endpoints. A patient-level met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
238
1
27

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(279 citation statements)
references
References 18 publications
(46 reference statements)
13
238
1
27
Order By: Relevance
“…While the mean insulin doses increased in both treatment arms, there was a tendency for a larger increase with Gla‐300, consistent with findings reported for the overall EDITION population 14, 15, 16. Although speculative, one possible reason underlying this greater increase in dose with Gla‐300 than Gla‐100 may be related to the lower bioavailability of Gla‐300, owing to the greater stability of its subcutaneous depot that might make it more prone to enzymatic inactivation compared with Gla‐100 18. It is also important to consider that the dose changes observed may be a consequence of the treat‐to‐target design of the EDITION trials; dose increases were to be expected given that participants switched to, or initiated, a new basal insulin in this study because they were uncontrolled on their previous treatment.…”
Section: Discussionsupporting
confidence: 84%
“…While the mean insulin doses increased in both treatment arms, there was a tendency for a larger increase with Gla‐300, consistent with findings reported for the overall EDITION population 14, 15, 16. Although speculative, one possible reason underlying this greater increase in dose with Gla‐300 than Gla‐100 may be related to the lower bioavailability of Gla‐300, owing to the greater stability of its subcutaneous depot that might make it more prone to enzymatic inactivation compared with Gla‐100 18. It is also important to consider that the dose changes observed may be a consequence of the treat‐to‐target design of the EDITION trials; dose increases were to be expected given that participants switched to, or initiated, a new basal insulin in this study because they were uncontrolled on their previous treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Данные трех клинических исследований EDITION (1, 2 и 3) с участием лиц, страдающих СД-2, также опу-бликованы в составе patient-level-метаанализа [102][103][104]. Следует подчеркнуть, что метаанализ на основе индивидуальных данных пациентов превосходит мета-анализ интегральных данных в случае потенциального модифицирующего влияния характеристик пациента на терапевтический эффект исследуемого воздействия [70,121].…”
Section: № 8(72) • 2015unclassified
“…Следует подчеркнуть, что в объединенном анализе СД-2-исследований (EDITION-1, 2 и 3, 6-месячные данные) [102][103][104] риск ночных подтвержденных и тя-желых гипогликемий уменьшался на 31 % у участни-ков, леченных Gla-300 с большей на 12 % дозой инсу-лина и меньшим увеличением веса.…”
Section: № 8(72) • 2015unclassified
See 1 more Smart Citation
“…In the randomized, controlled Phase III EDITION clinical trial program, Gla-300 was shown to be non-inferior to Gla-100 in reducing HbA1c levels, without increasing the risk of hypoglycemia versus Gla-100 in patients with type 1 diabetes (T1D) or T2D at 6 months [11][12][13][14] and at 1 year [15,16]. The proportion of patients who experienced ≥1 confirmed (blood glucose [BG] ≤70 mg/dL) or severe nocturnal hypoglycemic event was significantly lower for Gla-300 than for Gla-100 [17]. Data from the EDITION clinical trial program also supports the use of Gla-300 in different patient populations, its ease of use in insulinnaïve patients, and less hypoglycemia when switching from twice-daily insulin [11][12][13]15,16].…”
Section: Introductionmentioning
confidence: 99%